Reconfiguring Boundaries in Maryse Condé's Crossing the Mangrove - Deborah B. Gaensbauer (Studies in 20th & 21st Century Literature, 2004)
Maryse Condé's 1989 novel, Crossing the Mangrove, presents a compelling performance of the complicated patterns of place and space inherent in the social masquerade of a small, isolated, Guadeloupean village. Because the novel corresponds to Condé's return to a Caribbean "stage" to continue a long process of questioning mapped configurations of identity, critical attention has focused on the character of Francis Sancher, the returning "stranger," whose wake serves as both frame and catalyst for the action. Insufficient attention has been paid to the role of Mira Lameaulnes, Sancher's rejected mistress and the mother of his child, whose story the novel to a significant extent becomes as she effectively invades and undermines Sancher's role as the principal signifying figure. This reading foregrounds Mira's critical confrontation with notions of place and space as an illustration of Condé's revolutionary approach to invalidating static or formulaic treatments of Antillean sites of identity.
Keywords: Maryse Condé; Crossing the Mangrove; place; space; society; identity; Carribean; Antillean identity